Khitanan Massal Wujud Kepedulian kepada Anak-Anak di Desa Meranjat 1 dalam Rangka Pengabdian KKN Angkatan 59 UM Palembang - Dientyah Nur Anggina; Muhammad Dzaky Habiburrahman; Memo Naufal Othman; Agung Andriansyah; Amanda Mutia Carissa; Ando Anggara; Rizanti Fadilah Azzahra; Vino Regustian Saputra; Hany Pratiwi; Wira Swari; Muhammad Arga Aryo Saleh; Juan Fahirza Putra; Verdirian Toni (Jurnal Abdimas Kesehatan (JAK), 2023)
Community service which was synergized with the 59th KKN activities of UMPalembang has a great impact on the community to solve problems, especially in the health sector. Cost factors can affect the implementation of child circumcision in the village of Meranjat 1. Circumcision can prevent phimosis which can cause infection of the genitals of infants and children. The purpose of this community service activity was to improve the health status and the growth of Indonesian children, especially children in the village of Meranjat 1. The method were that children are carried out health screening and asked to urinate before circumcision, the implementation of circumcision using the cautery method and manual circumcision, giving medicine along with an explanation of how to use it, giving an explanation of post-circumcision control, giving contact numbers if there were complaints and giving souvenirs. The result of this activity was that 13 children participated in mass circumcision. The circumcision process went smoothly and the child's condition was healthy before, during and after circumcision. Public enthusiasm was very high. This activity was expected to continue so that it can reduce urinary tract infections in Meranjat I village